Supervisors’ Perspectives on Online Interprofessional Supervision: Results from a Mixed-Methods Longitudinal Cross-Sectional Study - Kari Almendingen; Torhild Skotheim; Ellen Merethe Magnus (Education Sciences, 2022)
Collaboration in interprofessional collaboration (IPC) teams is a part of working in welfare services. Unlike uniprofessional supervision, interprofessional supervision involves supervisors and students with different educational backgrounds. This study explores 105 supervisors’ responses after synchronous supervision of 15,700 students from teaching, health, and social work education programs who participated in an annual preservice interprofessional learning (IPL) course from 2018 to 2022. The purpose was to explore supervisors’ experience of the online IPL supervisor role and of the student’s learning outcomes through a longitudinal mixed-methods repeated design. Response rates: 61%, 45%, 82% and 40%, respectively. The students worked in IPL groups with limited interaction with supervisors, using a case-based learning approach. The supervisors were supportive of IPL but suggested changes to increase relevance. The imbalance in the knowledge base on child-related topics and IPL preparedness among the student groups was challenging. Some questioned the need for supervision, whereas others were concerned about the limited time allocated for supervision. We conclude that online supervision is forward-looking because candidates must prepare for helping users, such as children and their next-of-kin, online. We deduce that online supervision is relevant for the future and less complicated than IPL supervision